|:2,5
![n^4-2n^2-8=0 n^4-2n^2-8=0](https://tex.z-dn.net/?f=n%5E4-2n%5E2-8%3D0)
Пусть n^2=x, тогда n^4=x^2
![x^2-2x-8=0 x^2-2x-8=0](https://tex.z-dn.net/?f=x%5E2-2x-8%3D0)
![D=4+4\cdot8=36 D=4+4\cdot8=36](https://tex.z-dn.net/?f=D%3D4%2B4%5Ccdot8%3D36)
![x_{1}=\frac{2+6}{2}=4 x_{1}=\frac{2+6}{2}=4](https://tex.z-dn.net/?f=x_%7B1%7D%3D%5Cfrac%7B2%2B6%7D%7B2%7D%3D4)
![x_{2}=\frac{2-6}{2}=-2 x_{2}=\frac{2-6}{2}=-2](https://tex.z-dn.net/?f=x_%7B2%7D%3D%5Cfrac%7B2-6%7D%7B2%7D%3D-2)
Составим и решим систему уравнений:
n^2=4
n^2=-2 (квадрат не может быть отрицательным числом)
![n_{1}=2 n_{1}=2](https://tex.z-dn.net/?f=n_%7B1%7D%3D2)
![n_{2}=-2 n_{2}=-2](https://tex.z-dn.net/?f=n_%7B2%7D%3D-2)
___________________________________________________________________________
(2х-7)2-11(2х-7)+30=0
2х-7=3 1/3
2x=10 1/3
x=5 1/6
___________________________________________________________________________
9(9-5х)2+17(9-5х)+8=0
18(9-5x)+17(9-5x)+8=0
9-5x=- 8/35
-5x=-9 8/35
x=(323*5)/35
x=46 1/7